Anaerobic respiration: In vitro efficacy of Nitazoxanide against mitochondriate Acanthamoeba castellanii of the T4 genotype - Aqeel, Yousuf; Siddiqui, Ruqaiyyah Bano *; Farooq, Maria; Khan, Naveed Ahmed * (Elsevier, 2015)
Acanthamoeba is an opportunistic protist pathogen that is responsible for serious human and animal infection. Being one of the most frequently isolated protists from the environment, it is likely that it readily encounters microaerophilic environments. For respiration under anaerobic or low oxygen conditions in several amitochondriate protists, decarboxylation of pyruvate is catalyzed by pyruvate ferredoxin oxidoreductase instead of pyruvate dehydrogenase. In support, Nitazoxanide, an inhibitor of pyruvate ferredoxin oxidoreductase, is effective and non-mutagenic clinically against a range of amitochondriate protists, Giardia intestinalis, Entamoeba histolytica and Trichomonas vaginalis. The overall aim of the present study was to determine in vitro efficacy of Nitazoxanide against Acanthamoeba castellanii. At micromolar concentrations, the findings revealed that Nitazoxanide neither affected A. castellanii growth or viability nor amoeba-mediated host cell monolayer damage in vitro or extracellular proteolytic activities. Similarly, microaerophilic conditions alone had no significant effects. In contrast, microaerophilic conditions together with Nitazoxanide showed amoebicidal effects and inhibited A. castellanii-mediated host cell monolayer damage as well as extracellular proteases. Using encystation assays, it was observed that Nitazoxanide inhibited trophozoite transformation into cysts both under aerophilic and microaerophilic conditions. Furthermore, pre-treatment of cysts with Nitazoxanide inhibited A. castellanii excystation. These findings are important in the identification of potential targets that could be useful against parasite-specific respiration as well as to understand the basic biology of the life cycle of Acanthamoeba.